Knowledge, attitude, and practice of exclusive breastfeeding among mothers of childbearing age - Abdulwali Sabo; Justina Abba; Usman Sunusi Usman; Ibrahim Musa Saulawa; Majdi M. Alzoubi; Khalid Al-Mugheed; Samira Ahmed Alsenany; Sally Mohammed Farghaly Abdelaliem (Frontiers Media S.A., 2023)
BackgroundThe American Academy of Pediatrics and the World Health Organization recommend exclusive breastfeeding (EBF) for up to 6 months. Despite the importance of breast milk, EBF is far less prevalent in Nigeria than is recommended for developing countries. Worse still, the odds of EBF practice are very low in rural communities. Hence, the aim of this study was to assess the knowledge, attitude, and practice of EBF as well as identify the factors associated with EBF practice among mothers of childbearing age in Chamo town, Jigawa State, Nigeria.MethodsThe study is a cross-sectional design using a questionnaire to assess the required information. The methodology involved the use of simple random sampling to select mothers of reproductive age from Chamo town, which is a rural community located in Jigawa State, Nigeria. A semi-structured questionnaire was used to assess the mother's knowledge, attitude, and practices regarding EBF. Simple and multiple logistic regression analyses were performed to determine the factors associated with the practice of EBF.ResultsA total of 400 mothers between the ages of 18 and 41 took part in the study. More than half of the participants (57.8%) were between the ages of 26 and 33 and had a primary level of education (30.5%). Only 26.8% of the respondents practice EBF. Those with a tertiary education (AOR = 10.00, p < 0.001), civil servants (AOR = 12.51, p < 0.001), those aware of EBF (AOR = 3.65, p = 0.002), those with correct EBF knowledge (AOR = 4.61, p < 0.001), those with a positive attitude toward EBF demand (AOR = 0.51, p = 0.050), and those who received encouragement from their community (AOR = 9.87, p < 0.001) were more likely to practice EBF.ConclusionThe findings of the study revealed that the majority of the respondents' knowledge, attitude, and practice of EBF were minimal. This shows the need to step up efforts to educate mothers about the advantages of EBF for both their own health and that of their children while they are in the hospital recovering from childbirth.